The economics of happiness and anger in North Africa - Nadereh Chamlou (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Economics has rediscovered happiness even though the discipline has always been about human wellbeing. A growing evidence suggests that happier people can be more productive and innovative, which leads to profitability and economic growth. Thus, there are concerted efforts to measure happiness and design policies to enhance it. Happiness metrics rank North African countries among the lowest, and worsening over time. This paper explores key contributing factors to decades of frustration and anger in North Africa, and how these sentiments play themselves out since the Arab revolutions. Though these societies are more than ever polarized along the secular/progressive and Islamist/conservative lines, any government must deliver on economic expectations that are surprisingly similar for both groups. Insights from happiness economics and models of successful countries can serve as guiding principles for reforms that can promote economic and non-economic dimensions of individual and communal wellbeing.
Keywords: 330; economics of happiness; Arab Spring; North Africa; Islamic economics; freedom; governance